THE RESPONSIBILITY OF INDEPENDENT IRAQI NEWSPAPERS IN PROMOTING THE VALUES OF CITIZENSHIP AND NATIONAL BELONGING IN THE SOCIETY: (An Analytical Study in the Opinion Articles in the Newspapers of Al-Sabah Al-Jadeed and Al-Mada) - AL-Falahi, Hussein Ali Ibrahim (ALBAHITH ALALAMI, 2019)
The research problem stems from a chief question: “What is the nature of the responsibility that «Al-Sabah Al-Jadeed» and «Al-Mada» Newspapers have undertaken in promoting the values of citizenship and national belonging in the society? The research aims to achieve a number of goals, including: Determining the most prominent themes that were emphasized in the opinion articles in these two newspapers within the framework of the responsibility of promoting the values ​​of citizenship and national belonging in society, and revealing the most prominent topics that were discussed in opinion articles in the two sample newspapers regarding the promotion of the mentioned values. This research is a descriptive research. It used the descriptive analytical survey method. Moreover, in order to achieve the research objectives, the content analysis tool was used. The research reached a set of results, the most important of which are: the focus of opinion articles in the two sample newspapers on (9) axes in relation to their responsibilities referred to, and those axes included (68) different topics that deal with the topic and its aspects, and focus of opinion articles in the two sample newspapers mainly on special topics The values ​​of citizenship and national belonging, while other topics identified were less important, and opinion articles in the two sample newspapers varied interest in the topics included in the themes identified.